DDPWM-based power conversion system using a matrix converter for an isolated power supply - Hanamoto, T.; Yamada, H.; Toosi, S.; Mailah, N. F.; M., Norhisam (The Japan Society of Applied Electromagnetics and Mechanics, 2015)
This paper presents a novel electrical power supply system for an isolated system using a matrix converter (MC). MCs are able to convert AC to AC power directly without DC link capacitors. In this paper the MC is used as the main conversion equipment, because arbitrary output, AC to AC and AC to DC, are obtained to use adequate switching pattern. In this paper one AC output with constant frequency, and two DC output for battery storages system is explained, as an example. Direct duty ratio pulse width modulation (DDPWM) is selected to achieve the desired output. In addition, fictitious reference iterative tuning (FRIT) is employed to design the controller gains. The validity of the proposed method is shown using MATLAB/Simulink simulation.